2018
DOI: 10.1007/s00221-018-5250-2
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive threshold hunting for the effects of transcranial direct current stimulation on primary motor cortex inhibition

Abstract: Primary motor cortex excitability can be modulated by anodal and cathodal transcranial direct current stimulation (tDCS). These neuromodulatory effects may, in part, be dependent on modulation within gamma-aminobutyric acid (GABA)-mediated inhibitory networks. GABAergic function can be quantified non-invasively using adaptive threshold hunting paired-pulse transcranial magnetic stimulation (TMS). The previous studies have used TMS with posterior-anterior (PA) induced current to assess tDCS effects on inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Consequently, conventional recruitment theory suggests that increasing the relative contribution of the late I‐waves to the descending volley by applying AP stimulation will increase the sensitivity of the associated MEP to activation of these intracortical circuits, producing greater inhibition (76). In support of this, several studies have reported that assessing SICI (9,77–81) and LICI (79) with an AP current results in greater levels of inhibition. While these findings support conventional recruitment theory, Cirillo and Byblow (79) also reported that preferential activation of late I‐waves (assessed using MEP onset latencies) only correlated with the magnitude of SICI measured with AP currents, whereas there was no relationship between SICI and I‐wave recruitment for PA currents.…”
Section: Evidence For the Independence Of I‐wave Circuits Activated With Different Current Directionsmentioning
confidence: 75%
See 1 more Smart Citation
“…Consequently, conventional recruitment theory suggests that increasing the relative contribution of the late I‐waves to the descending volley by applying AP stimulation will increase the sensitivity of the associated MEP to activation of these intracortical circuits, producing greater inhibition (76). In support of this, several studies have reported that assessing SICI (9,77–81) and LICI (79) with an AP current results in greater levels of inhibition. While these findings support conventional recruitment theory, Cirillo and Byblow (79) also reported that preferential activation of late I‐waves (assessed using MEP onset latencies) only correlated with the magnitude of SICI measured with AP currents, whereas there was no relationship between SICI and I‐wave recruitment for PA currents.…”
Section: Evidence For the Independence Of I‐wave Circuits Activated With Different Current Directionsmentioning
confidence: 75%
“…These include spinal cord recordings from the cervical epidural space (a, recreated from reference (8), with permission. Individual subject data shown), SMU recordings (b, recreated from reference (9), with permission. Individual subject data shown), SICF (c, recreated from reference (10), with permission.…”
Section: Introductionmentioning
confidence: 99%
“…One such mechanism is the role other GABA receptors involved in motor cortex plasticity such as GABA‐B receptors (McDonnell et al., 2006) may play in the categorization of responders and non‐responders following a‐tDCS. It has been recently reported that both GABA‐A and GABA‐B mediated inhibition may be associated with the modulation of CSE following a‐tDCS and ultimately the observed inter‐individual variability following a‐tDCS (Mooney et al., 2018). To our knowledge, investigation into differences in GABA‐B receptor activity in a‐tDCS responders versus non‐responders is yet to be conducted and may provide deeper insight in mechanisms behind inter‐individual variability to a‐tDCS.…”
Section: Discussionmentioning
confidence: 99%
“…Albeit small, the slightly greater SICI values in GABRA3 gene rs1112122 and rs4828696 SNPs ‘Variant expression’ subgroup compared to the ‘Normal expression’ subgroup following a‐tDCS may highlight a trend towards reduced ICI, the non‐significant findings do not support this (Figures 4c and 5c). With ICI mediated by GABA receptors other than GABA‐A (McDonnell et al., 2006; Mooney et al., 2018), investigation into SNPs in genes that encode for other GABA receptors, such as GABA‐B, may offer additional insight into this potential relationship between a reduced capacity for ICI and a‐tDCS responder categorization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation